If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1) = 0 Reorder the terms: x(1 + x) = 0 (1 * x + x * x) = 0 (1x + x2) = 0 Solving 1x + x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(1 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {0, -1}
| -4(2x+5)= | | 5a-3=3a+9 | | 3a+2=a+12 | | 4s-15s=88 | | 4s-15s= | | 6a=24-6a | | -900=-30(-5b) | | 5x-7=4x+1.5 | | (y+3)(2y-5)(2y+7)(y-3)=91 | | 10y-7y=1.8 | | 8(y+3)= | | 5x-12=3(x-2) | | 2x+1=5x+7 | | 3x-5=x+2 | | (3x+8)(3x-6)=52 | | 10x-2x=2*4x | | 4(n-2)=3(n+2) | | 4(n-2)=3n+6 | | -2+18-4d=60 | | 5n-4=3n+6 | | 2+6m-3m+7= | | -55+5y+4=2(5y-2)-2 | | 5(n+1)=25 | | 6T-16T=20 | | 7(x+9)=7x+7*9 | | 4(n+2)=8(n-3) | | 6x+101=13x-11 | | 99-2x=16x+19 | | 12-8x=64-36x | | -49-7x=7x+21 | | 4x+1=23 | | 93-3x=4x+16 |